(untitled) (Biological Sciences - PJSIR, 2002)
Tablets, both coated and non-coated were examined for the microbiological contamination, growth and survival. Bacteria such as KlebsieUa aerogenes, Bacillus cereus, Pseudomonas aeruginosa, and Staphylococcus aureus were dominated in all the samples screened. Fungi isolated were Penicillium chrysogenum, Aspergillus jlavus and some yeasts as Candida albicans and Saccharomyces spp. Total bacterial counts ranged from 2.0 x 103 to 8 x 107 colony forming units (CFU) per millilitre while mould units ranged from O .2 x 102 to 1.4 x 102 cfu/ml. The bacterial isolates were further found to be able to grow and utilize the drugs (tablets) as sole carbon and energy sources.